2013 Humaine Association Conference on Affective Computing and Intelligent Interaction 2013
DOI: 10.1109/acii.2013.123
|View full text |Cite
|
Sign up to set email alerts
|

Automated Coach to Practice Conversations

Abstract: Abstract-We present a real-time system including a 3D character that can converse, capture, analyze and interpret subtle and multidimensional human nonverbal behaviors for possible applications such as job interviews, public speaking, or even automated speech therapy. The system works in a personal computer and senses nonverbal data from video (i.e., facial expressions) and audio (i.e., speech recognition and prosody analysis) using a standard webcam. We contextualized the development and evaluation of our sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Researchers found that feedback of social signals during job interview training signifcantly improved in comparison to traditional methods of training. Similar results were found when attempting to improve communication skills in those with social impairments [60], public speaking [13,52,53], medical students [39], job interviews [3,9,31,32,[41][42][43]. However, no studies investigate whether social skills can be improved using automated feedback in the context of media skills training.…”
Section: Related Workmentioning
confidence: 61%
See 2 more Smart Citations
“…Researchers found that feedback of social signals during job interview training signifcantly improved in comparison to traditional methods of training. Similar results were found when attempting to improve communication skills in those with social impairments [60], public speaking [13,52,53], medical students [39], job interviews [3,9,31,32,[41][42][43]. However, no studies investigate whether social skills can be improved using automated feedback in the context of media skills training.…”
Section: Related Workmentioning
confidence: 61%
“…Studies using technology enhanced training have been successful in improving social skills or communication skills [31]. Researchers [27] developed My Automated Conversation CoacH (MACH).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation